Start Spreading the News: A Comparative Experiment on the Effects of Populist Communication on Political Engagement in Sixteen European Countries. (October 2018) - Hameleers, Michael; Bos, Linda; Fawzi, Nayla; Reinemann, Carsten; Andreadis, Ioannis; Corbu, Nicoleta; Schemer, Christian; Schulz, Anne; Shaefer, Tamir; Aalberg, Toril; Axelsson, Sofia; Berganza, Rosa; et al.
Although populist communication has become pervasive throughout Europe, many important questions on its political consequences remain unanswered. First, previous research has neglected the differential effects of populist communication on the Left and Right. Second, internationally comparative studies are missing. Finally, previous research mostly studied attitudinal outcomes, neglecting behavioral effects. To address these key issues, this paper draws on a unique, extensive, and comparative experiment in sixteen European countries ( N = 15, 412) to test the effects of populist communication on political engagement. The findings show that anti-elitist populism has the strongest mobilizing effects, and anti-immigrant messages have the strongest demobilizing effects. Moreover, national conditions such as the level of unemployment and the electoral success of the populist Left and Right condition the impact of populist communication. These findings provide important insights into the persuasiveness of populist messages spread throughout the European continent.